Factors affecting the incidence of hypertension in the elderly: A literature review - Annisa, Tia Nur; Siahaan, Joni; Kan, Achara; Sianwarta, Rattapong (Journal of Community Nursing and Primary Care, 2024)
Background: Hypertension is one of the most prevalent chronic conditions among older adults and represents a major contributor to cardiovascular morbidity and mortality worldwide. The occurrence of hypertension in the elderly is influenced by a complex interaction of lifestyle, psychosocial, behavioral, and environmental determinants that may affect blood pressure control and overall health outcomes. Objective: This study aimed to identify factors influencing the incidence of hypertension among elderly individuals through a comprehensive literature review. Methods: This study employed a literature review design following the PRISMA 2020 guideline to systematically identify, evaluate, and synthesize relevant evidence regarding determinants of hypertension among elderly populations. A comprehensive search was conducted in several scientific databases, including PubMed, ScienceDirect, and Google Scholar, using combinations of keywords related to hypertension, elderly populations, and associated risk factors. Studies published in peer-reviewed journals were screened based on predefined inclusion and exclusion criteria. Eligible studies were critically appraised using the Critical Appraisal Skills Programme (CASP) tool and synthesized using a narrative and thematic approach to identify major determinants associated with hypertension among older adults. Results: The review revealed that several interconnected factors contribute to the development of hypertension in the elderly. Lifestyle determinants such as unhealthy dietary patterns, physical inactivity, and obesity were consistently reported as primary contributors to increased blood pressure. Psychosocial factors, including limited family support and insufficient knowledge about hypertension, were also associated with poor disease management. Additionally, inadequate self-care practices and unfavorable environmental conditions, such as limited access to healthcare services and environments that do not support physical activity, were identified as important determinants influencing hypertension outcomes among elderly individuals. Conclusion: Hypertension in the elderly is influenced by a multifactorial interaction of lifestyle, psychosocial, behavioral, and environmental determinants. Comprehensive prevention and management strategies that integrate lifestyle modification, health education, strengthening family and social support, and improving elderly-friendly healthcare environments are essential to reduce hypertension risk and improve the quality of life among older adults.